BOUND STATE SOLUTION OF DIRAC EQUATION FOR SCARF POTENTIAL WITH NEW TENSOR COUPLING POTENTIAL FOR SPIN AND PSEUDOSPIN SYMMETRIES USING NIKIFOROV-UVAROV METHOD - Deta, U.A.; Suparmi, A.; Cari, C. (Jurnal Spektra, 2014)
Bound state solution of Dirac Equation for trigonometric Scarf potential with a new tensor coupling under spin and pseudospin symmetric limits are investigated using Nikiforov-Uvarov method. The new tensor potential proposed is inspired by superpotential form in SUSY quantum mechanics. The Dirac equation with trigonometric Scarf potential coupled by new tensor potential for the pseudospin and spin symmetric cases reduces to Schrodinger type equation with shape invariant potential since the proposed new potentials are similar to the superpotential of Scarf potential. The relativistic wave functions are exactly obtained eigenfunction of NU method in terms of Jacobi polynomials and the relativistic energy equation is exactly obtained by using eigenvalue of NU method in the approximation scheme of centrifugal term. The new tensor potential omits the energy degeneracy both for pseudospin and spin symmetric cases. Keywords: Scarf potential, new tensor coupling potential, spin and pseudospin symmetry, Nikiforov-Uvarof methods.